Attitudes to the police, 1979 (UK Data Service, 1981)
The questions cover attitudes to the police, satisfaction with police services, experience of burglary, police corruption, whether the police should be armed, and attitudes to ethical standards among professionals, demographics and attitudes to political and economic issues.